Aligning perspectives: retailers and Generation Z consumers in the second-hand fashion market - Toebast-Wensink, Annuska; Soyer, Mirella; Timmerman, Tijs; Hekkert, Marko P.; Van den Broek, Karlijn (Journal of fashion marketing and management, 2025)
This study explores the relationship between second-hand fashion retailers’ marketing tactics and the purchasing drivers of Generation Z (GenZ) consumers, defined as individuals born between the mid-1990s and early 2010s, in the Netherlands. This study aims to identify areas of alignment and misalignment between retailer marketing tactics and GenZ motivations.An exploratory qualitative approach was used, involving interviews with nine second-hand fashion retailers and 25 GenZ consumers. The GenZ sample included both experienced consumers (those who have purchased second-hand fashion at least once) and inexperienced consumers (those who have never purchased second-hand fashion). Data were analyzed using the SHIFT framework, which conceptualizes behavioral change toward sustainability.The study identifies five key gaps between retailers’ perspectives and those of GenZ consumers: (1) a misalignment of focus on rational and emotional drivers, (2) a convenience - expectations gap for offline retailers, (3) a trust gap for inexperienced consumers, (4) a digital disconnect for thrift stores and (5) a market segmentation perception gap.By offering a nuanced understanding of retailers’ marketing tactics and GenZ’s drivers to purchase second-hand fashion, this study offers a unique perspective while applying the SHIFT framework to the second-hand fashion context. The findings provide actionable insights for retailers aiming to better align their marketing tactics with GenZ’s preferences and contribute to the broader literature on sustainable fashion consumption.